IMPLEMENTASI SISTEM PAKAR UNTUK MENDIAGNOSA KERUSAKAN PRINTER JENIS CANON BJC-2100SP - chairani, chairani; Sriyanto, Sriyanto; ., Fitria (Jurnal Informatika, 2012)
Printer as the printing tool is already dominate several field, such as office, shop, school, university, educational institution, etc. In certain time, there must be trouble in printer using, just like another machines, damages. So that, no matter how hi-tech the printing tool, it must need the expert to fix the damages.Expert system transform the knowledge of the expert(s) to be a computer system that help general people to do anything like an expert. In this case, expert system is built to diagnose the damage of printer type Canon BJC-2100SP. This expert system will increase time of effort to diagnose the damage of the printer type Canon BJC-2100SP for computer technician, specially for printer type Canon BJC-2100SP. Keyword : Production system, expert system, Rule, Knowledge, Inference Engineering.